THE EFFECT OF INSTITUTIONAL IMAGE AND EDUCATIONAL COST ON STUDENTS' INTEREST IN STUDYING AT NAMIRA MADINA HEALTH COLLEGE WITH BRAND TRUST AS AN INTERVENING VARIABLE - Lidya Kesuma Sari; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (Bulletin of Engineering Science, Technology and Industry, 2026)
This study aims to determine the effect of institutional image and educational cost on student interest through brand trust. This is an associative study, and the data used are quantitative. The data were obtained from primary and secondary data. The analytical methods used were descriptive statistical analysis and structural equation modeling. The population and sample in this study consisted of 297 members of the Mandailing Natal Regency generation Z community. The sampling technique used was accidental sampling. The results of this study indicate that institutional image has a positive and significant effect on brand trust, institutional image has a positive and significant effect on student interest, educational cost has a negative but insignificant effect on student interest, educational cost has a negative and significant effect on brand trust, brand trust has a positive and significant effect on student interest, institutional image has a positive and significant effect on student interest through brand trust, and educational cost has a negative and significant effect on student interest through brand trust among the Gen Z community in Mandailing Natal Regency.